2018
DOI: 10.1016/j.myc.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Sporocarp δ15N and use of inorganic and organic nitrogen in vitro differ among host-specific suilloid fungi associated with high elevation five-needle pines

Abstract: δ15N and use of inorganic and organic nitrogen in vitro differ among host-specific suilloid fungi associated with high elevation five-needle pines."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…We do know that whitebark pine seedlings colonized with the ectomycorrhizal fungus Suillus sibiricus promote nitrogen uptake and biomass increases in seedlings planted in burn soil devoid of ectomycorrhizal fungi [52,53]. Asebrook et al [53] found that while survival was not enhanced on some sites in Glacier National Park by inoculation, height and stem diameter (not assessed here) increased with inoculation. Trusty and Cripps [54] found that over 90% of whitebark pine seedlings planted in a severe burn were colonized with ectomycorrhizal fungi after five years, however host specific fungi such as Suillus were severely reduced in comparison to the unburned adjacent site.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We do know that whitebark pine seedlings colonized with the ectomycorrhizal fungus Suillus sibiricus promote nitrogen uptake and biomass increases in seedlings planted in burn soil devoid of ectomycorrhizal fungi [52,53]. Asebrook et al [53] found that while survival was not enhanced on some sites in Glacier National Park by inoculation, height and stem diameter (not assessed here) increased with inoculation. Trusty and Cripps [54] found that over 90% of whitebark pine seedlings planted in a severe burn were colonized with ectomycorrhizal fungi after five years, however host specific fungi such as Suillus were severely reduced in comparison to the unburned adjacent site.…”
Section: Discussionmentioning
confidence: 73%
“…Benefits might be better tested on larger, more continuous and severe burns, as these can be devoid of ectomycorrhizal fungi [52]. We do know that whitebark pine seedlings colonized with the ectomycorrhizal fungus Suillus sibiricus promote nitrogen uptake and biomass increases in seedlings planted in burn soil devoid of ectomycorrhizal fungi [52,53]. Asebrook et al [53] found that while survival was not enhanced on some sites in Glacier National Park by inoculation, height and stem diameter (not assessed here) increased with inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…In the same cited study, Suillus colonized roots to a greater extent when the main supply of nitrogen was ammonium (NH 4 + ) rather than nitrate, and foliar δ 15 N was lower with ammonium (Hobbie et al 2008). Suillus species can metabolize a range of nitrogen sources including ammonium, nitrate, amino acids, dipeptides, and proteins, and this has been shown to be true for S. sibiricus (= S. americanus) as well (Keller 1996;Nygren et al 2008;Antibus et al 2018). While nitrogen levels were considered low in our P. albicaulis-Suillus system, δ 15 N values were comparable to those of high nitrogen treatments in other studies.…”
Section: Foliar Nutrient and Isotope Analysesmentioning
confidence: 91%
“…Few studies have documented how ectomycorrhizal colonization affects nutrient content or isotope abundance in seedlings in the greenhouse. Suillus species are particularly involved in the uptake of nitrogen (Keller 1996;Nygren et al 2008;Antibus et al 2018), and are prime candidates for exploring the dynamics of N and C flow in ectomycorrhizal systems. In our experiment, the concentration of foliar nitrogen in whitebark pine seedlings colonized by Suillus was 18% lower in sterilized soil and 8% lower in unsterilized soil compared to uncolonized controls; the actual foliar nitrogen concentrations were around 1.53-1.57% after six months.…”
Section: Foliar Nutrient and Isotope Analysesmentioning
confidence: 99%
See 1 more Smart Citation